2002
DOI: 10.1046/j.1464-5491.2002.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Less severe hypoglycaemia, better metabolic control, and improved quality of life in Type 1 diabetes mellitus with continuous subcutaneous insulin infusion (CSII) therapy; an observational study of 100 consecutive patients followed for a mean of 2 years

Abstract: In our cohort of Type 1 diabetic patients, we observed a substantial decrease of hypoglycaemia along with a significant fall of HbA1c. Quality of life on CSII was improved when compared with ICT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
91
1
15

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 25 publications
15
91
1
15
Order By: Relevance
“…It must be noted, however, that many of the studies included in these meta-analyses and for calculating cost-effectiveness were published several years before the introduction of currently available pumps, and, more importantly, these models have never been validated against real long-term prospective controlled trials, so their value is questionable. Furthermore, more recent studies show that CSII therapy is associated with fewer severe hypoglycemic events (A: 89; C: [92][93][94]. Even if these models were accurate, what is cost-effective in adults may not be cost-effective in children given the additional health team interventions required for children and their families.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…It must be noted, however, that many of the studies included in these meta-analyses and for calculating cost-effectiveness were published several years before the introduction of currently available pumps, and, more importantly, these models have never been validated against real long-term prospective controlled trials, so their value is questionable. Furthermore, more recent studies show that CSII therapy is associated with fewer severe hypoglycemic events (A: 89; C: [92][93][94]. Even if these models were accurate, what is cost-effective in adults may not be cost-effective in children given the additional health team interventions required for children and their families.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Muitos estudos confirmam a diminuição da hipoglicemia grave com a infusão contínua de insulina subcutânea comparada à terapia insulínica por injeções, muitas vezes alcançando reduções até de 70% (18)(19)(20)(21). Vale ressaltar que os valores encontrados nestes estudos diferem muito, principalmente por nem sempre se definir corretamente hipoglicemia grave, isto é, a necessidade de ajuda de terceiros e/ou uso de …”
Section: Discussão E Conclusõesunclassified
“…Many subsequent studies have confirmed the hypoglycemia-reducing effect of insulin pumps (2,(11)(12)(13), with typical reductions in frequency of severe hypoglycemia of ϳ70% compared with MDI.…”
mentioning
confidence: 90%